The Digital Transformation of Higher Education Teaching: Four Pedagogical Prescriptions to Move Active Learning Pedagogy Forward - Røe, Yngve; Wojniusz, Slawomir; Bjerke, Annette Hessen (Frontiers in Education, 2022)
The implementation of digital learning technologies in higher education is expected to improve the quality of teaching and facilitate more personalised, flexible, and student-centred approaches. Despite these predicted educational benefits, research shows that technology is predominantly used to support traditional teaching. Due to their opportunities to combine digital technology and face-to-face learning, blended learning designs are considered important in the digital transformation of teaching in higher education. The aim of this paper is to draw on what we know from the blended learning literature and introduce the notion of active digital pedagogies (ADPs). We suggest that there are formidable barriers that prevent the implementation of ADPs in higher education and propose relevant institutional actions.